Rancang Bangun Aplikasi Penyewaan Kendaraan Berbasis Web Menggunakan Metode Waterfall - Mohamad Bilal; Isa Faqihuddin Hanif (Journal of Information System Research (JOSH), 2025)
This research aims to design and develop a PHP-based vehicle rental application for PT. Duta Rental Mobil using the Waterfall method. The rapid advancements in information technology have transformed the operations of many businesses, including the vehicle rental sector. PT. Duta Rental Mobil currently manages rental data, vehicle inventory, and transaction reports manually, leading to inefficiency, potential errors, and a lack of data accuracy. This application is developed using PHP and MySQL, focusing on managing customer data, vehicle information, and transactions. With the expectation that computerized results will enhance operational efficiency, minimize errors, accelerate transactions, and provide accurate real-time information.